Potentials of Liquefied CCB Treated Waste Wood for Wood Preservation - Miha Humar (University of Zagreb, Faculty of Forestry and Wood Technology, 2011)
Recovered wood is frequently contaminated with biocides and therefore its use is limited. Even more, wood, impregnated with classical chromated copper arsenate (CCA) preservatives is classified as a hazardous waste, therefore solutions for reuse or recovery of this material are sought. One of the options, discussed in this paper is liquefaction and further applications of liquefied wood containing biocide remainings. In order to elucidate this possibilty, spruce and beech wood was impregnated with liquefi ed CCB treated and untreaded spruce wood of various concentrations and exposed to wood decay fungi according to the EN 113 procedure. In paralel, the leaching experiments (ENV 1250-2) were performed as well. The results do not clearly show that liquefied wood is bio-inactive. In most cases the mass loss by fungal attack is decreased compared to the untreated controls. On the other hand, copper leaching from spruce wood, impregnated with the liquefi ed CCB treated wood was significantly reduced. Thus, there are indications that the liquefied wood could be utilized as a binding agent for inorganic biocides.